To study the role of hysteroscopy and laparoscopy in the evaluation of infertility - Mali, Kimaya; Mohanty, Swadhin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Infertility is defined as a lack of conception after at least 12 months of unprotected intercourse. Hysteroscopy and laparoscopy are the two methods widely used in assessing tubal patency, endometriosis, for diagnosis and treatment of polycystic ovaries, tub ovarian mass, peritubal adhesions. This study strives to undertake an in depth analysis of infertility with the help of hysteroscopy and laparoscopy to give a lucid picture to establish a diagnosis and subsequent treatment for the same. Methods: This is a prospective study carried out in department of obstetrics and gynaecology at Dr. Babasaheb Ambedkar Central Railway Hospital, Mumbai in the year 2008. Women within the age of 20 to 40 with infertility were included in the study. Results: There were 50 patients in the study out of which 35cases were of primary infertility and 15 cases of secondary infertility. Most common age group was between 26 to 30 years in 42% cases. Hysteroscopy could detect abnormality in 12 cases (24%) and the most common finding being fibroid. Laparoscopy could detect pathology in 74% of cases and the commonest pathology being PCOS (28%). Conclusions: Hysterolaparoscopy is a very good diagnostic tool for identification of certain problems like endometriosis, adhesions near adnexa etc. which are difficult to diagnose by other imaging modalities and even it can be used as the operative tool in certain situations while undergoing diagnostic test.